IMPLEMENTASI KEBIJAKAN PENDIDIKAN INKLUSIF DI SEKOLAH DASAR : TANTANGAN DAN SOLUSI - Fikriatunnisa; Marchenda Amalia Hapsari; Zannuba Chofshof Yusman; Septi Fitri Meilana4 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the inclusive education policy in elementary schools, especially at SDN Dukuh 08. This study uses a case study paradigm and a qualitative methodology. Selection of subjects is predicated on consideration, namely one of the teachers in whose class there are children with special needs (ABK). Data is gathered by means of documentation, interviews, and observation. The results showed that: (1) The implementation of inclusive policies for children with special needs (ABK) includes teacher training, curriculum adaptation, and collaboration with the government, (2) The challenges are the shortage of special educators, lack of facilities and infrastructure, parental resistance, and lack of teacher understanding, (3) The positive impact is that teachers are more patient and creative, and regular students are inclusive of children with special needs (ABK).